Pelatihan E-Commerce (Digital Marketing) pada Umkm Kue Khas Desa Kayu Laut Mandailing Natal - Jureid, Jureid (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
This service aims to provide digital marketing/e-commerce training to Typical Cake MSME Business Actors in Kayu Laut Village, Panyabungan Selatan District, Mandailing Natal Regency so that after this training, business actors can take advantage of the potential of the digital/e-commerce market. This service uses the Asset Based Community Development (ABCD) method which focuses on developing the quality of the community's economic welfare by emphasizing the superiority of assets owned by the community. The stages in this service start with the preparation stage, until the termination stage. Where the process takes approximately two months. It was discovered that the typical cake MSMEs in Kayu Laut village, based on their marketing, still use conventional methods. So training is needed that aims to empower the Khas Cake MSMEs of Kayu Laut village with marketing methods through e-commerce/digital marketing. The training activities for this service were successfully carried out as evidenced by the enthusiasm of the participants in participating in the activities. The results of this activity show that after carrying out this activity, business actors already understand how important it is to adapt their insights to the times. You already understand how important it is to apply e-commerce to existing products. Also, they start to apply this knowledge with direct practice. By having a Facebook and Shopee page as a place to promote the cake products it sells. This activity, will and is expected to have implications for the future of the typical UMKM cake from Kayu Laut village.